ETR 300 : De Lima Launderette Centre / Hazliza Ismail ... [et al.] - Ismail, Hazliza; Mahmud, Raudzoh Wardah; Hazizi, Emma Koreensya; Ishak, Noor Hasnah; Abdul Wahab, Norjihan (2000)
De Lima Launderette Centre is proudly to serve a commercial and self-service laundry services. De Lima Launderette Centre is committed in providing a clean and safe environment to do laundry. With the 5 tenns i.e. competence, hygienic, fast, easy and friendly makes De Lima Launderette Centre differ from other laundry services. De Lima Launderette Centre has 8 washers and 8 dryers and takes around 25 minutes for washers and dryers are 16 minutes per cycle. You as a customer, can either bring your own washing powder or can get it from De Lima Launderette Centre counters since there are dispensers in the launderette.